Meningkatkan Kemampuan Motorik Halus Pada Anak Usia Dini Melalui Kegiatan Menganyam Dengan Menggunakan Media Loose Parts - Amaliyah, Windah; Annisa, Yulia Nur; Handayani, Dita; Kusumawati, Dian; Yuanita, Yenny (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to explain through weaving activities using loose parts media to improve fine motor skills of early childhood. This study is a Classroom Action Research with the Kemmis and MC Taggart research design. The subjects of this study were children of the Agniya Playgroup in Bandung City in the 2023/2024 academic year in group A aged 4-5 years totaling 11 children. In the implementation of this research, it was carried out in 2 cycles, there were 4 stages consisting of planning, action, observation and reflection. In cycle 1 there are 2 meetings, the first meeting will be held on May 20, 2024 and the second meeting will be held on May 22, 2024. Furthermore, in the second cycle there will also be 2 meetings, the first meeting will be held on May 27, 2024 and the second meeting will be held on May 30, 2024. Data collection techniques used observation and documentation with data analysis through the percentage of achievement or success of learning in groups. Based on the analysis of the results and discussion, it can be concluded that the application of weaving activities with loose parts media can improve children's fine motor skills at the Agniya Playgroup in Bandung City with a learning success rate of 75% or included in the category of Developing According to Expectations.